Another look at a model for evaluating interface aesthetics - Ngo, David Chek Ling; Byrne, John G. (Zielona Góra: Uniwersytet Zielonogórski)
Gestalt psychologists promulgated the principles of visual organisation in the early twentieth century. These principles have been discussed and re-emphasised, and their importance and relevance to user interface design is understood. However, a limited number of systems represent and make adequate use of this knowledge in the form of a design tool that supports certain aspects of the user interface design process.
Keywords: screen design; interface aesthetics; aesthetic measures; aesthetic characteristics; multi-screen interfaces